FRI0151 Protein inhibitor of activated stat3 prevents peripheral arthritis and gut inflammation by regulating th17/treg cell imbalance via stat3 signalling in mice model of spondyloarthritis. (12th June 2018) - Kwon, E.; Min, H.K.; Kim, M.Y.; Choi, J.; Lee, S.-Y.; Seo, H.-B.; Jung, K.; Na, H.S.; Ryu, J.-G.; Kwok, S.-K.; Cho, M.-L.; Park, S.-H.
Abstract : Background: Spondyloarthritis (SpA) is inflammatory arthritis, and interleukin (IL) −17 is crucial on pathogenesis of SpA. Type 17 helper T cell (Th17) is one of major IL-17 secreting cells. Signal transducer and activator of transcription (STAT)−3 signalling induces Th17 cell differentiation. Present study investigated the effect of protein inhibitor of activated STAT3 (PIAS3) on SpA pathogenesis. Methods: Curdlan was injected to SKG ZAP-70 W163C mice for SpA induction. Then PIAS3 or Mock vector was inserted to mice for 10 weeks. Clinical score and histologic scores of paw, spine, and gut were evaluated. Expressions of IL-17, tumour necrosis factor-α (TNF-α), STAT3, bone morphogenic protein (BMP) were measured. Confocal stain and flow cytometry were used to assess helper T cell differentiation. Results: PIAS3 significantly diminished the histological scores of paw and gut. PIAS3 group displayed lesser expression of IL-17, TNF-α, and STAT3 in the paw, spine, and gut. BMP-2/4 expressions were lower in spine of PIAS3 group. Helper T cell differentiation was polarised toward upregulation of regulatory T cell (Treg) and downregulation of Th17 in the PIAS3 mice. Conclusions: PIAS3 showed preventive effects in mice with SpA by suppressing peripheral arthritis and gut inflammation. Proinflammatory cytokines and Th17/Treg differentiation were controlled by PIAS3. Additionally BMPs were decreased in spine of PIAS3 mice. These findings suggest that PIAS3 could be a potential therapeutic choice of SpA treatment. References: [1] Smith JA, Colbert RA: Review: The interleukin-23/interleukin-17 axis in spondyloarthritis pathogenesis: Th17 and beyond. Arthritis & rheumatology2014, 66:231–41. [2] O'Shea JJ, Lahesmaa R, Vahedi G, Laurence A, Kanno Y. Genomic views of STAT function in CD4+ T helper cell differentiation. Nature reviews Immunology2011;11:239–50. [3] Miossec P, Korn T, Kuchroo VK: Interleukin-17 and type 17 helper T cells. The New England journal of medicine2009;361:888–98. [4] Ruutu M, Thomas G, Steck R, Degli-Esposti MA, Zinkernagel MS, Alexander K, Velasco J, Strutton G, Tran A, Benham H, Rehaume L, Wilson RJ, Kikly K, Davies J, Pettit AR, Brown MA, McGuckin MA, Thomas R. beta-glucan triggers spondylarthritis and Crohn's disease-like ileitis in SKG mice. Arthritis and rheumatism2012;64:2211–22. Acknowledgements: None Disclosure of Interest: None declared